Aspects related to adherence to antiretroviral therapy of people living with HIV in a health service in Joao Pessoa - PB - Felício, Isabela Motta (2022)
The aim of the study is to investigate and understand the process of non-adherence to antiretroviral treatment in HIV patients registered in the SAE/CTA in the city of João Pessoa -PB. This is a cross-sectional study, with a quantitative approach conducted from September to December 2021, where the CEAT-VIH, with Brazilian adaptation, was used to collect data regarding treatment adherence and a structured interview for sociodemographic data collection. The results showed that, of the 123 participants, the predominant age group was 30 - 39 years old (35.8%), with the majority being male (86.2%), homosexual (70.7%) and brown (58 .5%), with complete higher education (43.9%), employment relationship (87%) and prevailing family income of 1 to 3 times the minimum wages (59.3%). Most had a time of diagnosis between 6 months and 5 years (78.9%) and high adherence to ART (58.5%). Adherence to drug treatment is an important and complex topic, since it involves aspects such as comprehension and understanding the disease and medications.